Which expression is equivalent to 4(-2c) – c -6c 8c – 1 -9c 7c + 1 I’m not good at thi

Question

Which expression is equivalent to 4(-2c) – c

-6c

8c – 1

-9c

7c + 1
I’m not good at this stuff -_-

in progress 0
Nho 2 months 2021-07-30T00:34:36+00:00 2 Answers 3 views 0

Answers ( )

    0
    2021-07-30T00:35:50+00:00

    Answer:    -9c

    Step-by-step explanation:

    4(-2c) – c

    = -8c – c

    = -9c  

    -9c is the answer

    0
    2021-07-30T00:35:57+00:00

    Answer:

    none of those?

    Step-by-step explanation:

    4(-2c) = -8c

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )